(untitled) (Research, Society and Development, 2021)
The present work aimed to investigate the possible effects of writing a clinical case for the analyst and for transmission. For this, we undertook a theoretical research in psychoanalysis, which resulted in this essay. As results and discussions, we elaborated two sections. The first highlights the position of the clinical case as privileged and original in the development of psychoanalytic research, demarcating functions as from its writing, among them, interrogating the theory, problematizing the analytical encounter in its singular dimension and provide the anchorage for metapsychological constructions. In the second section, we discuss about the effects of the writing of the case for the psychoanalyst who in your writing composition work, can mourn the lived process, as part of a necessary elaboration for the dissolution of transferential logic. We also discuss how the transmission operates in its value of possibility/ incompleteness, marked by the real of the clinic. As final considerations, we highlight the not-all dimension of writing, above all the bet that we should not retreat in the face of the challenge of write the clinic.